Cognitive Modeling of Management Decision Making at Enterprises - Kadiyevskiy, V. A.; Perkhun, L. P. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
Management decision making process at enterprise is quite difficult and often weakly structured. Effective decision making requires accounting of many internal and external factors, quantitative and qualitative alike. For assessment of consequences of a management decision, use of alternative approach on the basis of methodology and tools of cognitive modeling will be expedient. Inclusion of 4 units in the cognitive map of management decision making process at an enterprise is proposed: “Commodity and services markets”, “External environment”, “Financing”, and “Information”. Impulse modeling was carried out by several scenarios. As a result, the following results were produced. The first impulse was directed to aging of information and technological basis or its setting out of operation, which decreased the speed of information exchange. The decreased speed of information exchange decreases key performance indicators of the enterprise. When of the possible solutions to improve this situation enhancement of the knowledge base is chosen, this management decision will allow to normalize operation of information facilities in the short-term period, and to lower costs of their replacement (or employ new or upgrade the skill existing personnel) in the long-run period. When the decision to upgrade personnel skills is taken, the resulting indexes of the enterprise performance will be significantly lower in comparison with the previous decision. However, when the situation of simultaneous improvement of database and personnel skills is modeled, this will have a much higher positive impact on the company’s performance in comparison with their single applications. The developed cognitive model and its implementation confirm that use of advanced mathematical tools can considerably simplify decision-making process at an enterprise.